Rwanda- Joint World Bank-IMF Debt Sustainability Analysis - World Bank; International Monetary Fund (World Bank, Washington, DC, 2019)
An updated joint assessment of Rwanda's debt sustainability suggests continued low risk of external debt distress. External debt burden indicators remain below risk thresholds, except for a short and temporary breach of debt service indicators in 2023, when the Eurobond issued in 2013 matures. The main risk to debt sustainability––and macroeconomic stability––remains external shocks. Balancing Rwanda's still-strong public investment needs with maintaining low risks of debt distress, the government is focused on carefully choosing the highest return projects, financed under the most favorable terms. These principles are laid out in Rwanda's Medium-Term Debt Strategy, as are options for help mitigating potential risks. More broadly, the government is focused on creating a larger and more diversified export base while encouraging more private investment, to help secure high and resilient growth over the long term. Forthcoming results of fiscal risk analysis will help identify if there could be additional contingent liabilities that should be included in the next DSA.